Domain-oriented variability modeling for reuse of simulation models. (April 2014) - Lee, Hyesun; Yang, Jin-Seok; Kang, Kyo Chul; Pyun, Jai-Jeong
Reusability is an important quality attribute for defense modeling and simulation (MS) due to the ever-changing combat simulations and new requirements. There has been research conducted worldwide for reusing simulation models. The methods proposed in these studies (including One Semi-Automated Forces (OneSAF)) support reuse of simulation components in the development of new models. As the reuse units in the existing methods are at the simulation component level, when existing components do not satisfy new simulation requirements, new components have to be developed and maintained separately from the existing ones. However, simulation components in the same domain tend to have common parts; behavior models for tactical missions and battlefield functions in the same domain are derived from the same tactical doctrine/manual, and thus they tend to have a common structure. There is a need for a new method to maximize reusability by providing "fine-grained" reuse, i.e. composing simulation components from reusable fine-grained modules (i.e. behaviors/functions). We address the problem by applying the product line engineering concept to the development of simulation components. Commonalities and variabilities (CVs) of domain-specific simulation requirements and CVs of tactical behaviors and battlefield functions are identified in domain-oriented variability modeling. Then, the CVs are used to design and implement domain-specific simulation component assets with domain-specific tactical behaviors and battlefield functions while embedding the identified variabilities. These domain-specific component assets are instantiated based on selections of variabilities and then integrated to develop a simulation model. Feasibility of the method was demonstrated in an infantry squad combat domain of the Republic of Korea armed forces.